The Influence Of Product Quality, Brand Image And Price Perception On The Decision To Purchase Iphone Products (Survey on Students of University Perjuangan Tasikmalaya): - Lesmana, Sandi; Karmila, Mila; Arif (Utami Publisher, 2024)
This research aims to determine the influence of Product Qualty, Brand Image and Price Perception on Purchasing Decisions for Smartphones and iphone products among students at the Tasikmalaya University of Perjuangan. The method used is quantitative with a research sample of 100 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 16.0. Based on the results of this research, it shows that Product Quality, brand Image and Price Perception simultaneously have a positive and significant effect on Purchasing Decisions. Product Quality partially has a significant effect on Purchasing Decisions. Brand Image partially has a significant effect on Purchasing Decisions. Price Perception partially has a significant effect on Purchasing Decisions.